IL‐22 sustains epithelial integrity in progressive kidney remodeling and fibrosis. Issue 16 (28th August 2018) - Weidenbusch, Marc; Song, Shangqing; Iwakura, Takamasa; Shi, Chongxu; Rodler, Severin; Kobold, Sebastian; Mulay, Shrikant R.; Honarpisheh, Mohsen M.; Anders, Hans‐Joachim
Abstract: IL‐22, a member of the IL‐10 cytokine family, accelerates tubule regeneration upon acute kidney injury, hence we speculated on a protective role also in chronic kidney disease. We quantified intrarenal IL‐22 expression after unilateral ureteral (UUO) in wild‐type mice and performed UUO in IL‐22 knock‐out animals. Obstruction phenotypic differences between IL22 +/+ and IL22 −/− mice were assessed by histology, immunohistochemistry, immunofluorescence as well as western blotting and reverse‐transcriptase quantitative PCR ex vivo . Additionally, we performed in vitro experiments using both murine and human tubular cells to characterize IL‐22 effects in epithelial healing. We found increasing IL‐22 positivity in infiltrating immune cells over time upon UUO in wild‐type mice. UUO in IL22 −/− mice caused more tubular cell injury as defined by TUNEL positive cells and loss of tetragonolobus lectin staining. Instead, tubular dilation, loss of CD31+ perivascular capillaries, and interstitial fibrosis were independent of the Il22 genotype as assessed by standard histology, immunostaining, and mRNA expression profiling. In vitro experiments showed that recombinant human IL‐22 significantly enhanced human tubular epithelial cell proliferation and wound closure upon mechanical injury, and electric cell‐substrate impedance sensing studies revealed that recombinant IL‐22 sustained tubular epithelial barrier function upon injury. In contrast, IL‐22 had no such direct effects on human fibroblasts. Together, in progressive kidney remodeling upon UUO, infiltrating immune cells secrete IL‐22, which augments tubular epithelial integrity and epithelial barrier function, but does not affect vascular rarefaction or fibrogenesis. We conclude that IL‐22 could represent a molecular target to specifically modulate tubular atrophy. Abstract : In progressive kidney remodeling upon UUO, infiltrating immune cells secrete IL‐22, which augments tubular epithelial integrity and epithelial barrier function, but does not affect vascular rarefaction or fibrogenesis. IL‐22 could represent a molecular target to specifically modulate tubular atrophy.